Improving The Randomness of Output Sequence for The Advanced Encryption Standard Cryptographic Algorithm - Abdulbari Ali, Sherif (2005)
Rijndael, the Advanced Encryption Standard (AES) is an encryption standard uses ByteSub, Shiftrow, Mixcolumn and KeyExpansion functions which are the principle of generating a random and pseudorandom numbers. AES has larger S-boxes, but a very simple algebraic description that make it particularly vulnerable. Attacks against simplified variants of the AES algorithm have been reported for 128-bit keys, 7 rounds out of 10 have been attacked; for 192-bit keys, 7 rounds out of 12 have been attacked; for 256-bit keys, 9 rounds out of 14 have been attacked. NIST stated that AES appears to offer an adequate security margin. It is estimated that attacks in the indicated number of rounds above would result in a heavy cost to resources. Thus, it may be some time before malicious hackers have the ability to break AES in its original form. However, the rapid growth of computer technology and its resources may make this time shorter than NIST estimated time to break the algorithm. This research proposes a transformation function to be added to the AES algorithm. The new transformation function is shifting the columns of the AES state after the Mixcolumn function is applied to the state. This transformation function improves the security of the AES algorithm by increasing the randomness of the AES output sequence. The new approach has shown positive result in terms of the randomness of output sequence. The approach has increased randomness in comparison to the output sequence of the original AES algorithm.